Efek Protektif Ekstrak Etanol Umbi Bawang Dayak (Eleutherine bulbosa (Mill.) Urb.) terhadap Gambaran Histopatologi pada Sel Tumor Payudara Tikus Putih (Rattus norvegicus) Betina Galur Sprague Dawley Diinduksi 7,12 Dimethylbenz(α)Anthracene - Afifah Nurkarnia (Faculty of Medicine, Universitas Andalas, 2023)
Objective: To determine the effect of ethanol extract of dayak onion bulb on histology of mammary tumor cells in female Sprague Dawley rats strains that were induced by 7,12 dimethylbenz(α)anthracene (DMBA). Methods: The design of this study was a post-test only control group. DMBA (20 mg/kgBW) was given peroral twice a week for five weeks. In this research 30 female Sprague-Dawley rats were used and divided into 6 groups. Normal group weren’t treated DMBA; negative control group were treated DMBA and DMSO 5%; positive control group were treated DMBA and tamoxifen; treatment I group were treated DMBA and extract 180 mg/kgBW; treatment II group were treated DMBA and extract 360 mg/kgBW; and treatment III group were treated DMBA and extract 720 mg/kgBW. Results: There was significant difference between treatment I and negative control group (p=0,015); treatment II and negative control group (p=0,011); treatment III and negative control group (p=0,015). Conclusion: Ethanol extract of dayak onion bulb have an effect on histology of mammary tumors in female Sprague Dawley rats that were induced by 7,12 dimethylbenz(α)anthracene (DMBA).Keywords: Eleutherine bulbosa; Anti-cancer; Histopathology; Mammary tumor; 7,12 Dimethylbenz(α)anthracene